Implementation of physical, sports, and health education facilities - Dayanti, Jutri; Sumaryanto, Sumaryanto; Nanda, Fitri Agung (Jurnal Keolahragaan, 2021)
To the physical, sports, and health education, facilities have been one of the factors that support the successful assessment of learning results. with reference to the statement, the conduct of the study aims at identifying the implementation of Physical, Sports, and Health Education facilities management. During the conduct of the study, the subjects that had been selected were the Physical, Sports, and Health Education teachers and the School Principals of State 26 Elementary School and State 89 Elementary School in the City of Bengkulu. Then, the nature that had been adopted for the study was the qualitative research and the data were gathered by means of observation. During the observation, the notes on the condition, the inventory, the maintenance, and the implementation of the facilities management were collected. The results of the study show that the management of Physical, Sports, and Health Education facilities has not been properly implemented. The results have been confirmed by the following findings: (1) the condition of the existing Physical, Sports, and Health Education facilities is not fit for operation anymore; (2) the number of the Physical, Sports, and Health Education facilities is unfit; (3) the inventory for the Physical, Sports, and Health Education facilities is not properly implemented; (4) the awareness for maintaining the Physical, Sports, and Health Education facilities are low; and (5) the removal of the Physical, Sports, and Health Education is not implemented yet.